Odontogenic ameloblast-associated protein (ODAM) in gingival crevicular fluid for site-specific diagnostic value of periodontitis: a pilot study - Hye-Kyung Lee; Soo Jin Kim; Young Ho Kim; Youngkyung Ko; Suk Ji; Joo-Cheol Park (BMC, 2018)
Abstract Background Odontogenic Ameloblast-Associated Protein (ODAM) in gingival crevicular fluid (GCF) can provide evidence of the detachment of junctional epithelium from the tooth surface by periodontitis. This study sought to investigate the ability of ODAM to reflect the severity of periodontitis at a site-specific level; thus whether there was a relationship between clinical diagnostic parameters and the value of ODAM in GCF was analyzed. Methods Eight periodontitis patients with various severities were enrolled, and the clinical parameters and samples of GCF were obtained from 44 to 60 sites of each subject. The ODAM concentration was quantified by enzyme-linked immunosorbent assay. Correlation analyses between clinical parameters and ODAM values and unadjusted and adjusted (linear) mixed model analyses were performed. The accuracy of ODAM to reflect sites having a probing depth (PD) ≥ 5 mm and a positive bleeding on probing (BOP) was evaluated by receiver-operating characteristic analysis. Results A total of 424 GCF samples were collected. The mean ODAM concentration from each patient varied from 0.2 to 1.52 ng/ml. Correlations between PD or clinical attachment level (CAL) and ODAM values were found (p <  0.0001). An adjusted linear mixed model showed that PD or CAL were associated with ODAM values (p <  0.05). The area under the curve of ODAM, which reflected sites with PD ≥ 5 mm and positive BOP, was 0.661 (p <  0.0001). Conclusion This result shows the possibility of GCF ODAM as a site-specific biomarker for periodontal tissue destruction.